THE EFFECT OF HONEY AS NATURAL PRESERVATIVE TO QUALITY OF MEAT WITH TEMPERATURE VARIATION ON THE SAVE 4⁰C - Falensio Yano Karo; Permata Ika Hidayati; Aju Tjatur Nugroho Krisnaningsih (Jurnal Sains Peternakan, 2016)
The aim of this research was to determine the effect of honey as a natural preservative to the quality of meat with a temperature variation 4⁰C. The material used in this study was meat and honey with a concentration al 20 %. Honey used was wild honey, forest honey is honey produced by wild bees. This honey comes from wild bees called Apis dorsata. The research method is a laboratory experiment using a completely randomized design (CRD), which consists of 4 treatments with each treatment was repeated 3. The research variables there are two, namely the independent variable is the meat preservative given honey with a concentration of 20 % is kept by the variation shelf life, which is 0 hours, 24 hours, 36 hours, and 72 hours. Data were analyzed using analysis of variance when there are changes then followed by Duncan's test. The results showed that the preservation of ground beef with honey addition of 20 % with a variation of the storage period at TPC test results and protein levels resulted in a significant influence (P < 0.01). Preservation of meat no significant effect on the organoleptic (P > 0.05). TPC for the lowest value of the analytical results is 263.33 cfu / g at 24 hours storage time, the highest protein content on a storage time of 36 hours by 14.14 %, while the highest panelist preferences based on storage time 0 hours on the texture of ground beef by 86 %. The results of research carried out can be concluded that giving honey to 20% with a shelf life of 24 hours gives the best quality minced meat at a temperature 4⁰C. The addition of 20 % honey as a preservative in ground beef can maintain a shelf life of up to 72 hours to be consumed. Keywords: Minced Beef, Honey, storage, Total Microbe.